Transcatheter Aortic Valve Replacement-Associated Acute Kidney Injury: An Update - Rivera, Frederick Berro (Archīum Ateneo, 2023)
Background Transcatheter aortic valve replacement (TAVR) is a relatively novel minimally invasive procedure for the treatment of symptomatic patients with severe aortic stenosis. Although it has been proven effective in improving mortality and quality of life, TAVR is associated with serious complications, such as acute kidney injury (AKI). Summary TAVR-associated AKI is likely due to several factors such as sustained hypotension, transapical approach, volume of contrast use, and baseline low GFR. This narrative review aims to present an overview of the latest literature and evidence regarding the definition of TAVR-associated AKI, its risk factors, and its impact on morbidity and mortality. The review used a systematic search strategy with multiple health-focused databases (Medline, EMBASE) and identified 8 clinical trials and 27 observational studies concerning TAVR-associated AKI. Results showed that TAVR-associated AKI is linked to several modifiable and nonmodifiable risk factors and is associated with higher mortality. A variety of diagnostic imaging modalities have the potential to identify patients at high risk for development of TAVR-AKI; however, there are no existing consensus recommendations regarding their use as of this time. The implications of these findings highlight the importance of identifying high-risk patients for which preventive measures may play a crucial role, and should be maximized. Key Message This study reviews the current understanding of TAVR-associated AKI including its pathophysiology, risk factors, diagnostic modalities, and preventative management for patients.